Effect of Ultrasound-Assisted Pretreatment on Extraction Efficiency of Essential Oil and Bioactive Compounds from Citrus Waste By-Products - Harloveleen Kaur Sandhu; Prachi Sinha; Neela Emanuel; Nishant Kumar; Rokayya Sami; Ebtihal Khojah; Amina A. M. Al-Mushhin (Separations, 2021)
Waste or by-product use is in focus for reducing the environmental threat and acquiring wealth out of waste. The current study aim was to investigate the effects of ultrasound pretreatment on the extraction of bioactive compounds and composition of essential oils extracted from citrus waste. The response surface methodology (RSM) was used to optimize higher yield extraction parameters. Pretreatment of ultrasound-assisted extraction recovered 33% enhanced yield with reduced time and was economical as compared to conventional hydro-distilled process. The functional quality of essential oil was determined using FTIR and GC-MS. Antioxidants from citrus peel and pulp/pomace were extracted and analyzed by spectroscopic techniques. The quantification of bioactive compounds from citrus waste was performed using high performance liquid chromatography (HPLC). Mass transfer rate of antioxidants from peel and pomace were 30% increased as a result of ultrasound-assisted treatment. The significantly (p ≤ 0.05) higher TPC (735.54 mg/100 g) and antioxidant activity (44.26%) was recorded in Citrus sinensis Pulp and peel respectively. The bioactive compounds such as hesperidin (31.52 mg/100 g) was significantly higher in (p ≤ 0.05) in Citrus sinensis pulnd extract. Vanillin was found 1.21 mg/100 g in peel extract of citrus fruit, moreover vanillin was not detected in pulp extract. Myrecitin was not detected in both the samples. The bioactive natural compounds extracted from citrus peel can be used in food and pharma sector as natural anti-oxidantcompounds.